Mechanical and tribological properties of nano-sized Al2O3 particles on ADC12 alloy composites with Strontium modifier produced by stir casting method - Muhammad Wira Akira; Hanuna Haritsah; Anne Zulfia; Ekavianti Prajatelistia (ADI Journal on Recent Innovation, 2021)
Nano-Al2O3 particles were incorporated into ADC12 alloy with the addition of Al-5Ti-B, Al-Sr, and Mg to achieve high performance in mechanical and tribological properties. In this study, varied nano-Al2O3 was used from 0.25 vf-% to 0.5 vf-% through stir casting methods to discover the optimum amount to obtain high performance. Besides, the inclusion of grain refiner Al-5Ti-B and microstructure modifier Al-Sr is expected to improve performance to the next level. However, porosity and agglomeration still be a concern in Aluminum alloy matrix composite fabrication. The presence of spinel phase MgAl2O4 in the interface area between nano-Al2O3 particles and ADC12 alloy is relied upon to minimize this porosity and agglomeration issue. The optimum of tensile strength and hardness was found at 0.35 vf-% Al2O3 and wear rate at 0.4 vf%. Although, the optimum point of wear found at 0.4 vf%, porosity began to increase at 0.4 vf% as well. As a result, 0.35 vf% addition of the nano-Al2O3 gives the best performance for the composite.